Autonomous aerobatic flight of a fixed wing unmanned aerial vehicle - Hough, Willem J. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.